The dry forests and woodlands of Africa: managing for products and services - Chidumayo, E.N.; Gumbo, D.J. (Earthscan, 2010)
The dry forests and woodlands of Sub-Saharan Africa are major ecosystems, with a broad range of strong economic and cultural incentives for keeping them intact. However, few people are aware of their importance, compared to tropical rainforests, despite them being home to more than half of the continent's population. This unique book brings together scientific knowledge on this topic from East, West, and Southern Africa and describes the relationships between forests, woodlands, people and their livelihoods. Dry forest is defined as vegetation dominated by woody plants, primarily trees, the canopy of which covers more than 10 per cent of the ground surface, occurring in climates with a dry season of three months or more. This broad definition - wider than those used by many authors - incorporates vegetation types commonly termed woodland, shrubland, thicket, savanna, wooded grassland, as well as dry forest in its strict sense. The book provides a comparative analysis of management experiences from the different geographic regions, emphasizing the need to balance the utilization of dry forests and woodland products between current and future human needs. Further, the book explores the techniques and strategies that can be deployed to improve the management of African dry forests and woodlands for the benefit of all, but more importantly, the communities that live off these vegetation formations. Thus, the book lays a foundation for improving the management of dry forests and woodlands for the wide range of products and services they provide.